2021
DOI: 10.20535/2218-930022021241332
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Features of Nickel-Modified Mordenite Zeolites

Abstract: Zeolites are wide used materials in a range of processes of chemical, petrochemical, and nutritional industry. They are the active catalysts and sorbents, in particular, zeolites are characterized by high efficiency towards extraction of heavy and radioactive metals from the aqua medium. An important factor of high zeolite catalyst activity is preserving the integrity of the crystal structure. The purpose of this research was to check out the features of MOR zeolite modifications with nickel by means of low te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…2 takes up a position near 425 cm -1 . Comparison of R 560/425 in the spectra of the modified samples with that for the native rock, similar to that described earlier, 27 showed that the γ crystallinity of the mordenite component of the modified catalysts is generally retained (Table 1).…”
Section: Characterization Of the Samplessupporting
confidence: 76%
“…2 takes up a position near 425 cm -1 . Comparison of R 560/425 in the spectra of the modified samples with that for the native rock, similar to that described earlier, 27 showed that the γ crystallinity of the mordenite component of the modified catalysts is generally retained (Table 1).…”
Section: Characterization Of the Samplessupporting
confidence: 76%